The Diverse Roles of the Mucin Gene Cluster Located on Chromosome 11p15.5 in Colorectal Cancer - Gan, Guo-Lian; Liu, Jing; Chen, Wen-Jia; Ye, Qian-Qian; Xu, Ya; Wu, Hua-Tao; Li, Wei (Frontiers in Cell and Developmental Biology, 2020)
Colorectal cancer (CRC), the third most common malignant tumor in the world, shows multiple complex and pathologies based on the impaired structure and function of the intestinal mucosal barrier. Goblet cells secrete mucins, which are involved in the formation of the intestinal mucosal barrier and not only lubricate and protect the intestinal mucosa but also participate in the processes of cell adhesion, intercellular signal transduction, and immune regulation. It is accepted that the disordered expression and dysfunction of mucins are associated with the occurrence and development of CRC. This article focuses on the secretory mucins encoded by a gene cluster located on chromosome 11p15.5 and systematically reviews their composition, regulation, function, and role in CRC, to deepen the understanding of the pathogeneses of CRC and to provide a new basis and ideas for the treatment of CRC.